Third party autograph letter from Prince Pál Antrel (Paul Anton) Esterhazy - Esterházy, Paul Anton, Fürst 1786-1866:::Creator:::::::::::: (2021)
Third party autograph note in an unidentified hand, 1 leaf (2 written pages, with address on verso), in English, from Prince Pál Antrel Esterhazy to a Mr. Jordon thanking him for a favor.